Koli woman wearing Managalsutra - Mumbai Archive Project Team (Jio Institute, 2024)
The gaathla, also known as the mangalsutra, is a long necklace with multiple strands of black beads interspersed with gold (on the right). The mangalsutra is an essential piece of jewellery for married women, worn from the day of their wedding throughout their married life. There are two versions: a simpler one (on the left) for daily use and a longer, more elaborate one for special occasions and festivals (on the right).